Statistical optimization of a podoviral anti-MRSA phage CCASU-L10 generated from an under sampled repository: Chicken rinse - Abd-Allah, Israa M.; El-Housseiny, Ghadir S.; Al-Agamy, Mohamed H.; Radwan, Hesham H.; Aboshanab, Khaled M.; Hassouna, Nadia A. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The insurgence of antimicrobial resistance is an imminent health danger globally. A wide range of challenging diseases are attributed to methicillin-resistant Staphylococcus aureus (MRSA) as it is weaponized with a unique array of virulence factors, and most importantly, the resistance it develops to most of the antibiotics used clinically. On that account, the present study targeted the optimization of the production of a bacteriophage active against MRSA, and evaluating some of its characters. Methods and results The bacteriophage originated from a quite peculiar environmental source, raw chicken rinse and was suggested to belong to Podoviridae, order Caudovirales. It withstood a variety of extreme conditions and yield optimization was accomplished via the D-optimal design by response surface methodology (RSM). A reduced quadratic model was generated, and the ideal production conditions recommended were pH 8, glycerol 0.9% v/v, peptone 0.08% w/v, and 107 CFU/ml as the host inoculum size. These conditions led to a two-log fold increase in the phage titer (1.17x10¹² PFU/ml), as compared to the regular conditions. Discussion To conclude, statistical optimization successfully enhanced the output of the podoviral phage titer by two-log fold and therefore, can be regarded as a potential scale-up strategy. The produced phage was able to tolerate extreme environmental condition making it suitable for topical pharmaceutical preparations. Further preclinical and clinical studies are required to ensure its suitability for use in human.